1986
DOI: 10.1295/polymj.18.417
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Spontaneous Polarization in Fast-Quenched Copolymers of Vinylidene Fluoride and Trifluoroethylene

Abstract: ABSTRACT:Fast quenching from the melt was found to effect greatly the structures and ferroelectric properties of vinylidene fluoride and trifluoroethylene copolymers (P(VDF /TrFE)) in contrast to slow cooling. The results are discussed for high-and low-VDF content divided at about 50 mol% VDF. For the high-VDF copolymers, the quenched samples showed high T, like poled samples, implying an ordered ferroelectric phase. Poling the quenched samples at elevated temperatures produced a ferroelectric polarization the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Oka et al17 explained that in fast quenching, a sample passes through a high‐temperature region too fast to induce nucleation in an appreciable amount; hence, nucleation mostly proceeds at low temperatures. In slow‐cooling, on the other hand, a sample stays in a high‐temperature region during cooling long enough to complete nucleation at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Oka et al17 explained that in fast quenching, a sample passes through a high‐temperature region too fast to induce nucleation in an appreciable amount; hence, nucleation mostly proceeds at low temperatures. In slow‐cooling, on the other hand, a sample stays in a high‐temperature region during cooling long enough to complete nucleation at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The remanent polarizaagreement with the work of Tanaka et al 22 and others. 12,13 These authors concluded that an ortion measured from the first cycle of poling was considerably larger (Ç 100 mC/m 2 ) than that dered ferroelectric phase is formed when the copolymer is crystallized with large undercooling, seen in copolymer films prepared by slow cooling from the melt, after six cycles ( Ç 75 mC/m 2 ; see below T c . The response of ordered ferroelectric copolymer films subjected to electric field poling cy- Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 These copolymers also show increases in ied by many researchers. Oka et al 12 and Yang and the Curie transition temperature as the vinyliChen 13 have shown that although PVDF samples dene fluoride content increases. [7][8][9] In addition, prepared by crystallization from the melt generally they generally crystallize from the melt into a result in formation of the nonpolar phase II, which crystal form analogous to the polar phase I or bmust then be mechanically oriented in order to produce the polar phase I, thin films (õ30 mm) prepared by rapid quenching from the melt to infrared (FTIR) studies show that subsequent anstructure of the ferroelectric phase in P ( VDFTrFE) strongly depends on the crystallization nealing of these samples for 50 h at 120ЊC results in a complete transformation to phase I.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations